Shorebirds Breed in Unusually High Densities in the Teshekpuk Lake Special Area, Alaska - Andres, Brad A.; Johnson, James A.; Brown, Stephen C.; Lanctot, Richard B. (ARCTIC, 2012)
On the Arctic Coastal Plain of the National Petroleum Reserve-Alaska (NPR-A), the Teshekpuk Lake Special Area (TLSA) was recognized to protect outstanding wildlife values. Although information has accumulated on the TLSA’s value to caribou and waterfowl, its importance to breeding shorebirds remains largely unquantified. Therefore, we undertook a broad-scale ground study to estimate the population size and density of shorebirds breeding in the TLSA. From a series of plot surveys conducted from 2006 to 2008, we estimated a detection-adjusted total breeding population of more than 573 000 shorebirds and an overall density of 126 shorebirds/km2. Most shorebird species had their greatest densities on the Outer Coastal Plain or had approximately equal densities on Outer and Inner Coastal Plains; only two species had their greatest densities on the Inner Coastal Plain. The greatest densities of breeding shorebirds occurred immediately around Teshekpuk Lake. The TLSA supported more than 10% of the biogeographic populations of black-bellied plover (Pluvialis squatarola), semipalmated sandpiper (Calidris pusilla), and dunlin (C. alpina). Breeding shorebird density in the TLSA is one of the highest in the NPR-A, on Alaska’s North Slope, and throughout the circumpolar Arctic. Our results, coupled with previous information on waterfowl and caribou, indicate that the area around Teshekpuk Lake and the recognized goose molting area northeast of the lake should be protected from oil and gas development. Sur la plaine côtière arctique de la réserve pétrolière nationale-Alaska (NPRA), la région spéciale du lac Teshekpuk (TLSA) a été créée dans le but de protéger les valeurs exceptionnelles de la faune. Même s’il existe beaucoup d’information sur la valeur du caribou et de la sauvagine de la TLSA, l’importance qu’elle revêt en matière d’oiseaux de rivage nicheurs demeure peu quantifiée. Nous avons par conséquent entrepris de faire une étude sur le terrain à grande échelle pour estimer la taille et la densité de la population ...